An unusual case of chronic ectopic pregnancy - Prasad, Anima; Kumar, Amrish (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Thirty-seven years old P3A1L3 patient presented to our outpatient department with pain abdomen for 20 days. Thirty-five days back she had taken MTP kit and then after one week, D&C was done at a primary care centre, presuming incomplete abortion. After this, she developed abdominal distension and couldn’t pass motions. Then she went to some other health care centre and few investigations were done, there. USG showed bulky, excessively enlarged uterus with echogenic material in endometrium, Molar pregnancy, Endometrial mass, Left sided grade 2 hydronephrosis. After exploratory laparotomy, left sided salpingectomy was done. Histopathology report was consistent with ectopic pregnancy.